Expression, characterization and homology modelling of a novel hormone-sensitive lipase like-esterase from Glaciozyma antarctica PI12 - Mohamad Tahir, Hiryahafira (2020)
Microbial lipolytic enzyme, especially from extreme cold places such as Antarctica, has gained attention to study on their characterization and structure properties. Furthermore, there are many reported information on the isolation and production of an esterase from psychrophile which also useful in the industrial application. However, there are less reported enzyme from Antarctica especially from psychrophilic yeast due to low production level of wild strain and the cost to grow the wild strain at low temperature is quite expensive. Therefore, this project is conducted to focus on cloning, optimization expression, purification, biochemical characterization and structural prediction of esterase from psychrophilic yeast. Previously, a psychrophilic yeast was isolated from Antarctic sea ice and was identified as Glaciozyma antarctica PI12 and the genome was successfully sequenced and annotated. Several low identity gene encoding putative lipolytic enzyme were identified. These genes include a putative esterase that belongs to HSL like-esterase known as GlaEst12. Gene analysis reveals that GlaEst12 encoded for 399 of amino acids and has 30 % identity with chain A of bacterial hormone-sensitive lipase of E40 and belongs to H group since it has conserved motif HGGG and GDSAG at the amino acid sequences. GlaEst12 was expressed in the form of inclusion bodies and successfully purified via one-step Ni-Sepharose affinity chromatography with the final yield and fold of 38.91 and 1.72 respectively. The biochemical characterization of GlaEst12 showed novel properties since the optimal temperature range 50-60 °C and stable at alkaline pH condition. Unlike another HSL like-esterase, this esterase showed higher activity towards medium-chain ester substrates rather than shorter chain ester. Besides that, this esterase was activated when treated with metal ions (Na+, K+, Ca2+ and Mn2+) and stabilized when incubated with 1-propanol and toluene. Homology modelling of GlaEst12 was performed by Robetta software and using crystal structure of esterase 40 from HSL family as template. The 3D structure was predicted as a homodimer in which each monomer composed of N-terminal and C-terminal domain and have a typical α/β hydrolase fold with the catalytic residues found at Ser232, Glu341 and His371. The analysis of the structure and characterization of this esterase may provide new insights about the enzyme characteristics, especially from HSL like-esterase of psychrophilic yeast.